(untitled) (Delta Medical College Journal, 2016)
Background: Tuberculous Mastitis (TM) is a rare form of tuberculosis, even in countries where the burden of tuberculosis is high. It may mimic other systemic illness, even carcinoma breast, a condition with which it may coexist. Objective: To disseminate the message to the concerned expertise that it can present a diagnostic problem on radiological and microbiological investigations, and thus a high index of suspicion is needed. Materials and method: This observational study was carried out in the department of Surgical Oncology of National Institute of Cancer Research & Hospital (NICRH), Dhaka, Bangladesh from January 2010 to December 2015. During the study period only five cases of TM were identified and all were included in the analysis purposively. Results: Mean(±SD) age of the patients was 27.2(±16.22) years. AFB in pus was found in one patient. Fine Needle Aspiration Cytology (FNAC) was done in four AFB negative patients and granulomatous lesions were found in each case. Histopathological examinations of two resected breast lumps also showed granulomatous lesions consistent with tuberculosis. Breast ultrasound showed multilocular abscess with ill-defined lump in two cases, solitary lump in two patients and cystic lesion in one patient. Axillary lymphadenopathy was found in one patient with solitary lump. Repeated image guided aspiration of the abscess was performed in 3 cases. Two patients underwent lumpectomy operation. All five patients were given anti-TB chemotherapy for 6 months. All of them recovered fully after completion of Category I treatment. Conclusion: Though it is a great mimicker with proper evaluation the disease is curable with antitubercular drugs, and in some cases surgery is required. Delta Med Col J. Jul 2016 4(2): 67-70